1999
DOI: 10.1097/00054725-199905000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cigarette Smoking on Cytokine Levels in Patients with Inflammatory Bowel Disease

Abstract: Anecdotal reports suggest that smoking may be beneficial for patients with inflammatory bowel disease (IBD) as nicotine may act through inflammatory mediators within the colonic mucosa. Furthermore, there is increasing evidence that cytokines play a pathologic role in IBD. Our aim was to determine the effects of cigarette smoking on cytokine levels in the colonic mucosa of patients with and without IBD. Mucosal biopsies were obtained from 10 patients with Crohn's disease (CD), 10 with ulcerative colitis (UC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…1997). Other studies showed negative correlations between IL‐8 levels and smoking (Sher et al. 1999).…”
Section: Discussionmentioning
confidence: 90%
“…1997). Other studies showed negative correlations between IL‐8 levels and smoking (Sher et al. 1999).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, chronic smoking is characterized by abnormal inflammatory response since the cigarette component have many physiological activities. Clinical study showed that gingival crevicular fluid IL-4, IL-6 and IL-8 were significantly increased in the smoking periodontitis individuals compared with non-smoking periodontitis individuals (26), and smokers with ulcerative colitis had higher serum IL-1ÎČ and IL-8 than the non-smokers with ulcerative colitis (27). Experiment in vitro found that cigarette smoke extract (CSE) could promote human macrophage-like cells producing IL-8 and TNF-α (28), and dose-dependently increased IL-8 and IL-6 release in primary human airway epithelial cells (29).…”
Section: Controlsmentioning
confidence: 95%
“…IL-8 is also known to be increased in the mucosa of UC and CD patients [7,8,9,10]. A study reported that CS affects IL-8 levels in the mucosa of UC and CD patients [141]. Of course, the gut is a very complex organ system with complex functions (e.g.…”
Section: Impact Of Cs On Trp Channels In the Gut?mentioning
confidence: 99%